CLINICAL ASPECTS AND MORPHOFUNCTIONAL FEATURES OF THE THYROID GLAND - JO’RAYEVA FARANGIZA ERKINOVNA (TADQIQOTLAR, 2025)
Abstract: The influence of thyroid hormones on the formation of the brain has been  shown  by  numerous  classical  studies.  However,  the  presence  of  neurons, astrocytes and microglia in the brain The 2021 release of TRα and TRβ receptors was associated  with  low  TSH  levels  and  poorer  performance  on  tests  of  cognitive development in older adults with a mean age of (49.5 ± 7.4) years, without overt thyroid dysfunction.